2020
DOI: 10.1111/1467-9566.13101
|View full text |Cite
|
Sign up to set email alerts
|

Delivering healthcare’s ‘triple aim’: electronic health records and the health research participant in the UK National Health Service

Abstract: The UK National Health Service (NHS) is changing. Consecutive UK industrial strategies have supported the shift from an NHS that provides free‐at‐point‐of‐delivery healthcare to one that also facilitates research. Said to promote healthcare’s triple aim of ‘better health, better healthcare, and lower cost’ (Wachter, 2016, 3), the digitisation of patient records is a core part in opening routine aspects of the health system to potential research. In this paper, we thematically analyse 11 policy documents and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research. This would complement efforts to improve people’s access to their own data 79…”
Section: Discussionmentioning
confidence: 99%
“…As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research. This would complement efforts to improve people’s access to their own data 79…”
Section: Discussionmentioning
confidence: 99%
“…The reimagining and reconfiguring of the public hospital also has political‐economic implications. Drawing on the work of Birch and others (Birch, 2017; Birch & Muniesa, 2020), authors have argued that the digitalisation of healthcare services including the NHS reflects the ongoing assetization characteristic of contemporary OECD economies (Vezyridis & Timmons, 2021; Wyatt, Lampon, and McKevitt, 2020). In effect, digital systems generate data as an asset for realising value in health care, research and finance.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this represents one of the first large-scale initiatives of this kind in Italy, both in the private and in the public healthcare sector, and probably the first one in Southern Italy. Indeed, in spite of its renowned national healthcare system in terms of human resources and quality of care, Italy still suffers from a longstanding delay in collecting, organizing and exploiting health big data, in contrast with other large-scale and established initiatives in Western countries which are supported by national healthcare systems, e.g., in the UK [ 24 ].…”
Section: Discussionmentioning
confidence: 99%